Efeito do jejum agudo no período ativo sobre os peptídeos gastrointestinais em mulheres eutróficas e com obesidade - Karin Alessandra Honorato (2023)
Introduction: Fasting practice has shown beneficial results concerning metabolic parameters and weight loss. This practice is often performed throughout the day during individuals daily life activities. Among the effects of fasting on intermediary metabolism, its potential to modulate the secretion of gastrointestinal peptides related to hunger control and metabolic regulation stands out. On the other hand, the effects of acute fasting during daily activities, unlike fasting during the night, and whether eutrophic and individuals with obesity respond in the same way are unknown. Objective: To investigate the effect of acute fasting during the active period on gastrointestinal peptides in eutrophic women and with obesity. Methods: This was a non-randomized clinical trial, stratified by nutritional status into two groups according to Body Mass Index (BMI): (i) eutrophic group (BMI > 18.5 kg/m² and < 24.9 kg/m²) and (ii) group with obesity (BMI > 35 kg/m²). The sample consisted of adult women aged 18 to 60 years. The initial evaluation was conducted in the morning after a 10-hour overnight fasting, during which the following measurements were taken, and personal data were collected: anthropometry, indirect calorimetry, and body composition. Participants had 5 mL of blood collected for the analysis of gastrointestinal peptides (GIP, GLP-1, PP, PYY, and ghrelin), adiponectin, insulin (glucose and HOMA indices). Then, a standardized breakfast with a caloric value corresponding to 20% of the estimated energy needs calculated after the initial data collection was provided. Afterward, the participants were released to perform their usual daily activities and were instructed to maintain fasting for 10 hours throughout the day. Participants returned at the end of the day for the repetition of the procedures performed in the initial assessment and blood collection. Statistical analyses were performed using the Statistical Package for the Social Sciences for Windows Student Version® (SPSS) version 20.0, and the graphs were created using the GraphPad Prism version 8.0.1 program, adopting a significance level of 5%. Results: 54 women were included in the study, with 29 in the eutrophic group and 25 in the group with obesity. Fasting during the active period led to a reduction in insulin and adiponectin concentrations and in HOMA-IR and HOMA-BETA indices, as well as an increase in circulating pancreatic polypeptide (PP), both in eutrophic women and with obesity. Only the group with obesity experienced a reduction in leptin and an increase in glucagon-like peptide-1 (GLP-1) after daytime fasting. Between the eutrophic group and with obesity, leptin and insulin concentrations were higher in the group with obesity after fasting during the active period. GIP, ghrelin, and peptide YY (PYY) did not show changes after fasting during the active period when compared to overnight fasting. Conclusion: Fasting during daily activities reduces anorexigenic hormones insulin and leptin. However, it also increases PP and GLP-1, especially in women with obesity. Fasting during daily activities may reorganize a complex network of endocrine signals that can somehow modulate homeostatic and hedonic eating behavior.